Pendampingan Belajar Bahasa Inggris Sekolah Dasar Dengan Metode Diskusi Dalam Di SDN Kotasari Pusakanagara - Dody Wahyudi Purnama (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
Assistance in learning English using the discussion method carried out by KKN Students of the English Language Education Study Program FKIP, University of Subang which was carried out at SDN Kotasari, Pusakanagara aims to foster interest and attractiveness of participants in learning English and to find out the significant effect of the discussion on students' vocabulary skills. For this study, 20 participants participated in 3 experimental groups. A total of 20 participants were tested using the direct discussion method. The data collection used in this activity was that students were asked to write down lists of words that had been determined and then discussed to measure the amount of participant vocabulary mastery and field notes, carried out by documenting the English learning process and photos of activities during the teaching and learning process both before and when the action was carried out. . Based on the mentoring activities that have been carried out, it can be concluded that there was a change in the attitude of the participants from those who were less active, not enthusiastic and less involved to become more active, enthusiastic and willing to interact collaboratively during the mentoring activities the students became more active and enthusiastic about learning English with the method discussion and have a positive impact on vocabulary skills.